(untitled) (Journal of Oriental Studies, 2016)
This article discusses conceptually significant symbolic and significantestimatedcharacteristicsof different colorsin the composition ofChineseproverbs, identifiedtheir ethnicrelevance,for comparis onresistant Kazakh folksayings.